Tree based land-use: An option for insulating farming from climate change - ., Doddabasawa; Chittapur, B.M. (Indian Journal of Agroforestry, 2020)
Climate change is sensitizing the whole world more than ever before through its vagaries on mankind and ecology, and therefore various efforts are made globally to reduce its negative impacts. Farming being targeted and also important cause of climate change warrants evolving technologies for on-farm mitigation and adaptation to these changes. These tree-based land-use systems with beneficial impacts can help insulate farming from vagaries and vicissitudes of climate besides diversifying income sources to small-holder and sequestering carbon (C). Tree-based land-use systems have high rate of C mitigation potential ranging from 0.29 to15.21 Mg haâˆ’1 yrâˆ’1. Besides, agroforestry system create microclimatic conditions such as reduced soil temperature and soil moisture evaporation, increased water availability and ground water recharge through reduced run off and higher infiltration which result in higher water use efficiency. Nutrient availability is also improved due to reduced soil erosion and nutrient leaching, and continuous addition of organic matter into the system under tree cover. That apart, increased employment and improved and diversified products hand-hold farmer during climate vagaries. Therefore, an effort was made to present the available information on the dynamics of tree-based land-use from the point of climate change and ecology.